The Rural and Peripheral in Regional Development : An Alternative Perspective - De Souza, Peter (Regions and Cities, 2018)
"The countryside has often been marginalized in discussions of economic and societal development, in favour of the urban. This book aims to stimulate a debate and a re-evaluation of how the concepts of the rural, peripheral and marginal are treated in academia and policy. Approaching this theme from geographic, demographic and economic perspectives, Peter de Souza makes a compelling case for giving the periphery a prominent role as an integral part of a holistic and balanced society. The book carefully deconstructs the concept of the urban, and critiques the idea of urban-rural or centre-periphery comparisons, and presents an alternative approach to spark future discussions.The Rural and Peripheral in Regional Development will be of interest to those studying and researching in the areas of rural economics, sustainability and development, as well as those involved in rural policymaking."--Provided by publisher.